Characterization of atmospheric aerosols with multiwavelength Raman lidar - Mueller, D.; Mattis, I.; Kolgotin, Alexei; Ansmann, Albert; Wandinger, U.; Althausen, D. (SPIE Proceedings, Lidar Technologies, Techniques, and Measurements for Atmospheric Remote Sensing III, 2007)
Multiwavelength Raman lidar observations have matured into a powerful tool for the vertical resolved characterization of optical and microphysical properties of atmospheric aerosol particles. Raman lidars that operate with laser pulses at three wavelengths are the minimum requirement for a comprehensive particle characterization. Parameters that are derived with such systems are particle backscatter and extinction coefficients, and particle extinction-to-backscatter (lidar) ratios. Effective radius and complex refractive index can be derived with inversion algorithms. In the past ten years we carried out regular observations over Leipzig, Germany, with multiwavelength Raman lidar. We could establish a time series of important aerosol properties. For instance, we find that pollution layers are present in the free troposphere in more than 30% of our observations in each year. These layers result from long-range transport of, e.g., forest-fire smoke from North America and Siberia, anthropogenic pollution from North America, Arctic haze from North polar areas, and mineral dust from the Sahara. Observations were also carried out with our mobile six-wavelength Raman lidar during several international field campaigns since 1997. Those data allow us to establish a first comprehensive overview on the vertical distribution of optical and microphysical particle properties in different areas of the world.